Formulation and Physical Evaluation of Orthosiphon aristatus Leaf Extract Granule Preparation as Herbal Beverage Candidate - Al-Hakim, Nur Achsan; Nur Fauziyyah, Salma Alifia; Purnamasari, Nira; Faramayuda, Fahrauk (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Developing Orthosiphon aristatus (Blume) Miq. leaf extract of purple varieties into granule dosage forms is expected to facilitate consumption, storage, and can extend the shelf life of the product. This study aims to develop the formulation and evaluation of granule preparations of O. aristatus leaf extract of purple varieties, with a comparison of lactose and maltodextrin fillers to produce the best formula. The granule dosage forms were prepared using wet granulation method. Furthermore, the variation of granule preparation formula consists of F1 (extract with lactose), F2 (extract with maltodextrin), F3 (extract with a combination of lactose and maltodextrin 1:1), F4 (freeze dried extract with lactose), F5 (freeze dried extract with maltodextrin), and F6 (freeze dried extract with a combination of lactose and maltodextrin 1:1). The physical evaluation of granules comprised moisture content testing, flowability, compressibility index, particle size distribution, and granule dissolving time. Results from the physical evaluation of granules over 28 days of storage indicated that all six formulas met the criteria for good granules, with F3 emerging as the optimal formula due to its superior physical stability and visually appealing appearance upon dissolution. To conclude, this study demonstrates that O. aristatus leaf extract can be effectively formulated into instant granule preparations suitable for herbal beverage or alternative medicine. Moreover, by modifying the filler material, the physical stability of the granule preparation can be maintained.